A comparison of 1995 WHO classification with 2003 ISN/RPS classification of lupus nephritis: a single centre observation - Chow, T.K.; Looi, L.M.; Cheah, P.L. (2015)
Background: In the past, lupus nephritis was histologically classified according to the 1995 WHO Classification. With the introduction of the 2003 ISN/RPS Classification, many nephropathology services converted to this new classification. This study was undertaken to compare both classification systems in a single centre practice. Methods: 103 consecutive adequate renal biopsies initially reported as lupus nephritis in the Department of Pathology, Faculty of Medicine, University of Malaya were reassessed using the criteria of both the 1995 WHO Classification and the 2003 ISN/RPS Classification. Results: The relative prevalence for each class using the WHO Classification were: Class I (1%), Class II (8.7%), Class III (6.8%), Class IV (60.2%), Class V (20.4%), Class VI (2.9%) while the prevalence using the 2003 ISN/RPS Classification were: Class I (1%), Class II (8.7%), Class III (6.8%), Class IV (61.2%), Class V (21.3%), Class VI (1%). Both classifications were essentially comparable with regards to Classes I, II and III. The differences in Classes IV, V and VI were significant in potential to alter patient management. The identification of segmental lesions (Class IV-S) over and above a global nephritis (Class IV-G) deserves more focused clinicopathological studies to gauge whether these groups have different clinical manifestations and outcomes. With regards Class V, the ISN/RPS system, by requiring that all mixed classes be stipulated in the diagnostic line, minimizes the chances of patients missing out on additional treatment. The ISN/RPS system has stricter criteria for Class VI, which again minimizes patients missing out on therapy. On the whole, the ISN/RPS system is more user-friendly as criteria are more clearly defined which translates to more benefits to patient care.